Estudo de otimização de um dispositivo para o aproveitamento da energia das ondas - João Marinheiro (2013)
Over the years, new technologies to exploit renewable energy sources (not exploited previously) were developed, allowingreducing the consumption of non-renewable energy resources such as oil, coal, natural gas, among others. In this sense, a newdevice was idealized, the CECO - Wave Kinetic Energy Converter, which aims at converting the kinetic and potential energy ofthe waves into electrical energy. This paper presents the optimization study of the CECO wave energy converter and givescontinuity to the work carried out by Teixeira (2012) that studied, for the first time, the performance and the feasibility of thisnew device. For that, a new physical model of CECO was constructed on a geometric scale of 1/20, which included severalchanges and improvements in relation to the previous model, especially in what concerns the geometry of the floatingelements, guiding of central rods, structural bars and cross-section of the central body.In the experimental study, several tools and advanced measurement and data analysis techniques were used, which allowedstudying the behavior of the device for different wave conditions and modes of operation, namely: damping levels introducedby Power Take Off (PTO), slope of the device, submersion levels of the floating elements and positions of the center gravity ofthose elements. The PTO system was also defined and characterized. Two different techniques were used to evaluate the powerabsorbed, one based on the direct measurement of the difference of potential produced by the PTO, and the other one,indirectly, based on the measurement of the device's response with a motion capture system and the PTO performance curves(previously determined). The calculated capture widths showed that the CECO concept is promising, thus justifying furtheroptimization studies.